1996
DOI: 10.1001/archinte.1996.00440170139015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Pseudomonas aeruginosa Bacteremia, With Special Emphasis on the Influence of Antibiotic Treatment

Abstract: The rate of P aeruginosa bacteremia is falling slightly at our hospital. The emergence of the human immunodeficiency virus epidemic has had a considerable impact on both epidemiology and mortality. The presence of severe underlying disease, surgery, pneumonia, and, especially, severe sepsis are associated with a poor outcome. With the exclusion of patients with intravenous catheter-associated P aeruginosa bacteremia, the administration of an appropriate antimicrobial therapy is essential to a good outcome. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Many studies have compared monotherapy with combination therapy for the management of nosocomial pneumonia, VAP, or bacteremia [65][66][67][68][69][70][71][72][73].…”
Section: Broad-spectrum Versus Narrow-spectrum Therapy and Monotherapmentioning
confidence: 99%
“…Many studies have compared monotherapy with combination therapy for the management of nosocomial pneumonia, VAP, or bacteremia [65][66][67][68][69][70][71][72][73].…”
Section: Broad-spectrum Versus Narrow-spectrum Therapy and Monotherapmentioning
confidence: 99%
“…seudomonas aeruginosa is a leading cause of nosocomial infections, which are often severe (26,43) and difficult to treat because of their limited susceptibility to antimicrobial agents (35) and the frequent emergence of antibiotic-resistant mutants during therapy (8). Factors related to the host, the organism, and the treatment may increase mortality.…”
mentioning
confidence: 99%
“…aeruginosa bacteremia [6-9,12,25,26]. In our study, inappropriate initial antibiotics were prescribed more frequently in the case group, but mortality was similar in the two groups.…”
Section: Discussionmentioning
confidence: 59%
“…Third generation cephalosporins are most commonly used to treat infectious complications in patients with liver cirrhosis, but their antimicrobial spectra against Pseudomonas aeruginosa are not identical to each other [3-5]. It has been reported that inadequate or delayed antibiotic therapy for pseudomonas bacteremia is associated with poor prognosis [6-9]. Hence, empirical antimicrobial therapy that lacks anti-pseudomonal activity could be harmful in case of pseudomonas bacteremia.…”
Section: Introductionmentioning
confidence: 99%